Just a Matter of Prospect (Theory)? - The Ecological Rationality of the Traditional Accounting Principles - Eduard Braun (Technische Universität Clausthal, Abteilung für Volkswirtschaftslehre, 2014)
The principles characterizing the traditional revenue-expense approach to accounting have never been “invented.” They are an institution that is the result of social evolution, not of human design. Therefore, the efforts to defend them against the balance sheet approach endorsed by standard-setters have encountered severe difficulties. The latter is based on a coherent model of the economy, namely neoclassical economics. This paper argues that a solid basis for explaining the rationale of the traditional accounting principles can be found in behavioral economics, especially in Prospect Theory. If one combines this result with a market process view of the economy, the revenue-expense approach turns out to be congenial to the organization of the market economy.
Keywords: D03; M41; M48; 330; Financial Accounting; Prospect Theory; Fair Value; Historical Costs